Systemic inflammation and oxidative stress post‐lung resection: Effect of pretreatment with N‐acetylcysteine. Issue 1 (27th October 2015) - Bastin, Anthony J.; Davies, Nathan; Lim, Eric; Quinlan, Greg J.; Griffiths, Mark J.
Abstract: Background and objective: N‐acetylcysteine has been used to treat a variety of lung diseases, where is it thought to have an antioxidant effect. In a randomized placebo‐controlled double‐blind study, the effect of N‐acetylcysteine on systemic inflammation and oxidative damage was examined in patients undergoing lung resection, a human model of acute lung injury. Methods: Eligible adults were randomized to receive preoperative infusion of N‐acetylcysteine (240 mg/kg over 12 h) or placebo. Plasma thiols, interleukin‐6, 8‐isoprostane, ischaemia‐modified albumin, red blood cell glutathione and exhaled breath condensate pH were measured pre‐ and post‐operatively as markers of local and systemic inflammation and oxidative stress. Results: Patients undergoing lung resection and one‐lung ventilation exhibited significant postoperative inflammation and oxidative damage. Postoperative plasma thiol concentration was significantly higher in the N‐acetylcysteine‐treated group. However, there was no significant difference in any of the measured biomarkers of inflammation or oxidative damage, or in clinical outcomes, between N‐acetylcysteine and placebo groups. Conclusion: Preoperative administration of N‐acetylcysteine did not attenuate postoperative systemic or pulmonary inflammation or oxidative damage after lung resection. Clinical trial registration:NCT00655928 at ClinicalTrials.gov Abstract : In a human model of lung injury and oxidative stress, preoperative administration of the antioxidant N‐acetylcysteine augmented plasma thiols but did not attenuate postoperative systemic inflammation or oxidative stress associated with lung resection.